Japanese ecosophy : a traveller's notes - Zaini Ujang, Prof. Dato' Ir. Dr., 1965-, author (Kuala Lumpur : Institut Terjemahan & Buku Malaysia ; Johor Bahru : Universiti Teknologi Malaysia, 2019)
This book is about Japanese ecosophy. The author shares his understanding of the features and components of Japanese thinking and lifestyle in relation to nature, environmentalism, and green practices through life experiences as a frequent traveller to Japan, and as a reputable scholar with special interest in water and environmental sustainability. The approach that the author has taken has been casual, personal, sometimes judgemental and less philosophical. This book contains personal narrative of events, stories, conversations and anecdotes on Japanaese values, attitudes, habids, characters and culture towards environmental sustainability.